FORECASTING OF PRODUCTION OUTPUT FOR LIGHT INDUSTRY ENTERPRISES WITH PURPOSE TO DETERMINE THEIR POWER RESOURCES REQUIREMENTS. Part 1 - V. N. Romaniuk; D. B. Muslina (Наука и техника, 2015)
The paper presents an interest for those specialists who are involved in solution of efficiency problems in light industry of Belarus as one of the significant industries that forms an economic situation in the Republic, its export potential and social climate. It is extremely relevant for the Belarusian enterprises to reduce production costs in order to preserve and strengthen positions in the light industry market. Operating capacities for production of natural, synthetic textile and knit-wear materials and their subsequent treatment are in many respects unjustifiably energy intensive. Nowadays the only acceptable solution of the problem for reduction of production costs is to decrease its energy component. Such approach requires transition to creation of modern heat and power supply systems at heat technology enterprises.The most important sub-system of the enterprises is own combined production of energy flows of secondary electrical and heat energy, freeze. There is a complex of problems that arise during designing process of tri-generation unit. One of the most important problems presupposes determination of a base load demand and capacity of every energy flow generated by an energy source. The solution is directly related to production output, which in its turn is determined by the requirements of sales markets. Due to various reasons the markets have their own specificity for the enterprises under consideration. It is proposed to use statistical methods for searching requirements. In this connection it is necessary to take into account industry development rate (pre-determined by State Programs, Plans, Governmental solutions, including directive instructions), production volumes of competitive goods and actual goods situation on the sales market.The paper presents the first part of the executed complex investigations which are directed on the development of scientifically-substantiated proposals for higher energy efficiency of the industry as a whole. It has become possible on the basis of the results obtained in the process of studying its power and heat engineering problems. The results of an analytical calculation analysis of statistical and obtained forecasting data are considered as a basis for the development of scientifically substantiated proposals for modernization of energy supply systems and power resource saving of the industry that fully corresponds to the investigation objective. The result of the executed investigations, that is a significant reduction of the energy component in the production costs will be presented in the follow-up publications.